Study on the monoclonal antibody to chlorpyrifos - JIN Ren-yao; GUI Wen-jun; WU Jian-xiang; WANG Chun-mei; ZHU Guo-nian (浙江大学学报. 农业与生命科学版)
One hybridoma cell line (1G10) secreting monoclonal antibody (McAb) against chlorpyrifos was produced by fusing mouse myeloma cells (SP2/0) with spleen cells from BALB/C which were immunized by the artificial antigen conjugated with bovine serum albumin (BSA). Isotype and subclass of the monoclonal cell (1G10) was classified as IgG1. The light chain of the McAb was indentified to be κ. Its titres of ascitic fluids were up to 1 × 10-6 by indirect ELISA. The inhibition rate of 50% of the McAb with the insecticide chlorpyrifos detected by ELISA was 80.8 μg·L-1, the McAb could specifically react with chlorpyrifos but no cross-reactivity to chlorpyrifos analogues.